High-speed Railway Passenger Flow Analysis Method and Platform Design Based on the Concept of One-Day-One-Plan. Issue 4 (October 2020) - Nie, Bowen; Nie, Lei; Fu, Huiling
Abstract: Based on the concept of One-Day-One-Plan, passenger demand should be considered different every day while timetable should also be adjusted according to passenger flow fluctuation. The analysis of passenger flow provides basis of line planning problem and train timetabling problem. This paper uses cluster analysis to integrate the characteristic of passenger flow data, designs and subdivides the service level of each OD. A data analysis platform connecting with Line Planning Section and Train Timetabling Section is developed to achieve the quick response of the real-time passenger flow fluctuation, ensure the supply-demand match and improve service level.